Propose Design of New Cross Section by Using One Dimensional HEC-RAS at Maran River, Pahang - Ahmad, Nurul Syuhada; Ahmad, Noor Aliza (Journal of Advancement in Environmental Solution and Resource Recovery, 2022)
Continuous rains in Maran, Pahang cause the river’s water capacity to increase and become more complex. The river system is important for controlling water distribution in terms of quantity, quality, time and system capability. The problem that arises is the river unable to accommodate large quantities of water that cause flooding at the research area. This study was conducted to analyze cross-section data and steady flow data at selected chainage in order to produce the river cross section and to solve flood problems by changing the sections of river channel by using HEC-RAS. All the data such as cross-section data, manning values, contraction and expansion data obtained from Maran Irrigation and Drainage Department while the discharge value was calculated using Rational Method for 10 years, 50 years and 100 years. From the result, the analysis of the cross section include with the affected area of floodplain was identified. According to the hydraulic model generated by HEC-RAS software, 9 of 10 stations found will be flooded since they were unable to accommodate the water flow. From this study, the modification of channels was proposed and the simulation of the new cross section showed that the channel can accommodate water flow till 100 years and not faced flood anymore. In a meantime, the DID department can prepared and give an early warning about the flood incident. It expected that the research area will not experience flooding as before